The Modi ‘Wave’: Implications of Uttar Pradesh State Elections - Sinderpal, Singh (2017)
The sweeping victory of PM Narendra Modi’s ruling party in Uttar Pradesh enhances its position in several states and the Upper House while auguring a stronger showing in the next general election. It also consolidates Modi’s dominant position in the BJP.